2010
DOI: 10.1261/rna.2393711
|View full text |Cite
|
Sign up to set email alerts
|

Substrate recognition by ribonucleoprotein ribonuclease MRP

Abstract: The ribonucleoprotein complex ribonuclease (RNase) MRP is a site-specific endoribonuclease essential for the survival of the eukaryotic cell. RNase MRP closely resembles RNase P (a universal endoribonuclease responsible for the maturation of the 59 ends of tRNA) but recognizes distinct substrates including pre-rRNA and mRNA. Here we report the results of an in vitro selection of Saccharomyces cerevisiae RNase MRP substrates starting from a pool of random sequences. The results indicate that RNase MRP cleaves s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 46 publications
(63 reference statements)
2
38
1
Order By: Relevance
“…4B; Chamberlain et al 1996;Coughlin et al 2008). This is in contrast to the cleavage preference recently determined for RNase MRP, which also does not show extensive requirements for cleaving naked RNA, but has a strong consensus for cytosine at position +4 relative to the cleavage site (Esakova et al 2011).…”
Section: Binding Of Single-stranded Rna To Rnase Pcontrasting
confidence: 78%
“…4B; Chamberlain et al 1996;Coughlin et al 2008). This is in contrast to the cleavage preference recently determined for RNase MRP, which also does not show extensive requirements for cleaving naked RNA, but has a strong consensus for cytosine at position +4 relative to the cleavage site (Esakova et al 2011).…”
Section: Binding Of Single-stranded Rna To Rnase Pcontrasting
confidence: 78%
“…3), where one Pop5/Rpp1 heterodimer bound one RNA molecule (the complex was formed at concentrations of RNA and proteins that were more than an order of magnitude higher than the dissociation constant [below], allowing us to estimate the stoichiometry of the RNA-protein complex). We did not observe the binding of the Pop5/Rpp1 heterodimer to control yeast tRNA or to 140-nt-long (mostly single-stranded) RNA containing a fragment of the internal transcribed spacer 1 (ITS1), a known substrate for RNase MRP (Esakova et al 2011, and references therein; data not shown). Our attempts to perform similar experiments using yeast RNase P RNA did not yield interpretable results, apparently due to misfolding of RNA; the same problem was encountered previously (Perederina et al 2007).…”
Section: Resultsmentioning
confidence: 88%
“…Footprinting studies of RNase MRP and RNase P holoenzymes suggest that the catalytic domain of RNase P and the corresponding domain of RNase MRP have similar structural organizations (Esakova et al 2008). The differences in the substrate specificities of RNases MRP and P (Esakova et al 2011) are likely to be due to the divergence in parts of their RNA components (Fig. 1A,B) and the presence of unique proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that RNase MRP has a limited sequence preference for a C at position +4 relative to the site of cleavage (Esakova et al 2011). This preference does not seem to occur with RNase P, which appears to recognize RNA with little regard to primary sequence (Marvin et al 2011).…”
Section: Discussionmentioning
confidence: 99%